2011
DOI: 10.1016/j.bbrc.2011.05.100
|View full text |Cite
|
Sign up to set email alerts
|

Differential heterocyclic substrate recognition by, and pteridine inhibition of E. coli and human tRNA-guanine transglycosylases

Abstract: tRNA-guanine transglycosylases (TGTs) are responsible for incorporating 7-deazaguanine-modified bases into certain tRNAs in eubacteria (preQ1), eukarya (queuine) and archaea (preQ0). In each kingdom, the specific modified base is different. We have found that the eubacterial and eukaryal TGTs have evolved to be quite specific for their cognate heterocyclic base and that Cys145 (E. coli) is important in recognizing the amino methyl side chain of preQ1 (Chen et al. (2011) Nuc. Acids Res.39, 2834). A series of mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Kinetic analysis of the human QTRT enzyme has shown that it exhibits similar K M and k cat values for both guanine and queuine as substrate ( 4 , 42 ), raising the question of how the enzyme exercises selectivity for the correct substrate. This anomaly has previously been explained by the irreversible nature of queuine-incorporation, which differs from guanine, which can be reversibly displaced after tRNA insertion ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Kinetic analysis of the human QTRT enzyme has shown that it exhibits similar K M and k cat values for both guanine and queuine as substrate ( 4 , 42 ), raising the question of how the enzyme exercises selectivity for the correct substrate. This anomaly has previously been explained by the irreversible nature of queuine-incorporation, which differs from guanine, which can be reversibly displaced after tRNA insertion ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…The side chain of the valine residue corresponding to Cys158 of Z. mobilis Tgt appears at a position where it might form an interaction with the dihydroxy-cyclopentenyl substituent. While Cys158 and Val233 are highly conserved in bacterial Tgt, the corresponding valine and glycine residues are invariant in all eucaryotic Tgt catalytic subunits whose sequences have been determined so far [42].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the side chain conformation of Thr159 induced upon preQ 1 binding may well be correlated with the reduced preQ 1 affinity observed upon mutation of Cys158 to valine. It should be noted, that Thr159 is in most eucaryotic Tgt catalytic subunits replaced by a nearly isosteric valine residue [42].…”
Section: Discussionmentioning
confidence: 99%
“…In culture, pterin was found to inhibit the formation of aspartyl Q-tRNA in mouse fibroblasts ( K i ~1 μM) [ 44 ]. More recently the inhibition of human queuine-insertase by biopterin was evaluated, yielding a K i of 8.9 μM [ 116 ]. Being an order of magnitude above the K m value for queuine (260 nM), this data would suggest that biopterin is not a particularly potent inhibitor of the enzyme [ 116 ].…”
Section: Queuine and Queuosine In Metabolism Development And Aginmentioning
confidence: 99%